2014
DOI: 10.4103/0973-029x.131896
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical characterization of cyclin dependent kinase-4 in different histological grades of oral leukoplakia and oral squamous cell carcinoma

Abstract: Background:Cyclin dependent kinase-4 (CDK4) encoded by CDK gene, is a heterodimer protein of cell cycle in G1-S transition. This study aimed to characterize the CDK4 immunoreactivity in different histological grades of oral leukoplakias (OLs) and oral squamous cell carcinomas (OSCCs) and also aims to discuss its probable role in the tumor biogenesis.Materials and Methods:Expression of CDK4 was investigated in total of 52 samples including OL (15), OSCCs (30) and normal oral tissues (07). A labeled Streptavidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Additionally, retinoids have long been implicated in regulating cell cycle events, specifically by inducing the degradation of various cyclins and cyclin dependent kinases (CDKs) (reviewed in [33]). Previous studies have reported overexpression of CDK4/6 in multiple tumor types including OSCC [7072]. An in vitro systematic substrate screen in several cancer-derived cells lines concluded that CDK4/6 can phosphorylate and stabilize FOXM1 to promote entry into the S phase of the cell cycle [73].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, retinoids have long been implicated in regulating cell cycle events, specifically by inducing the degradation of various cyclins and cyclin dependent kinases (CDKs) (reviewed in [33]). Previous studies have reported overexpression of CDK4/6 in multiple tumor types including OSCC [7072]. An in vitro systematic substrate screen in several cancer-derived cells lines concluded that CDK4/6 can phosphorylate and stabilize FOXM1 to promote entry into the S phase of the cell cycle [73].…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Miliani de Marval et al and Niwa et al have demonstrated that exposure of carcinogens such as 4‐nitroquinoline 1‐oxide and 7,12‐dimethylbenzanthracene (DMBA) in rats and transgenic mice resulted in the overexpression of CDK4 in pre‐malignant lesions . Similarly, the gradual increase in the expression of CDK4 through tissue samples ranging from hyperkeratosis, oral epithelial dysplasia (mild, moderate and severe) and OSCC has been demonstrated by Chen et al Furthermore, this evidence has been consolidated by a study conducted by Shyam et al whereby an immunohistochemical assay was conducted in samples of normal tissue, OPMDs (leukoplakia samples) and OSCC and a gradual increase in expression of CDK4 was found with increasing grades of dysplasia …”
Section: Expression Of Cdks In Opmdmentioning
confidence: 91%